A shield construction grouting slurry and preparation method thereof
Through the specific ratio of grouting slurry and modified fill fiber and polyacrylamide network structure, the problem of insufficient crack resistance and waterproofness of grouting slurry in shield construction is solved, and high-performance applications under complex geological conditions are achieved .
Patent Information
- Application Number
- CN202410831358.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The existing shield construction grouting slurry has insufficient crack resistance and water resistance in high-water content formations, and the ambient temperature and humidity have a great impact on performance, making it difficult to adapt to complex geological conditions.
A grouting slurry consisting of gel materials, river sand, fly ash, limestone powder, sodium-based bentonite, modified fill fibers and modified additives with specific ratios, and a multi-layered composite fiber structure is formed by modifying fill fibers. and modified polyacrylamide network structure to enhance adhesion and permeability resistance.
It significantly improves the crack resistance, water resistance, stability and temperature resistance of the grouting slurry, and enhances the application adaptability and performance in complex environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of shield construction materials, and in particular to a shield construction grouting slurry and a preparation method thereof. Background Art
[0002] When using the shield method to excavate subway tunnels and other underground structures, gaps will form between the shield tail and the newly installed tunnel segments during the advancement of the shield machine. In order to ensure the stability and waterproof performance of the tunnel structure, these gaps must be filled in a timely and effective manner. This process is called synchronous grouting. Therefore, grouting technology in shield construction is a key link to ensure tunnel stability and prevent groundwater leakage. Traditional grouting slurry is mainly composed of cement, fly ash, sand, water and various additives, and its ratio needs to be precisely controlled to meet the construction requirements under different geological conditions.
[0003] With the gradual development of rail transit construction across the country, choosing reasonable grouting slurry according to different address conditions has become the preferred solution for shield construction operations. However, there are some obvious problems with existing grouting slurries. For example, because the existing grouting slurries are too concerned about the cost of raw materials, their crack resistance and waterproofness are insufficient. Especially in soil systems such as sand and gravel strata with high water content, the slurry is prone to cracks after solidification and has poor waterproofness, which greatly affects the sealing and stability of the tunnel. The rapid penetration of water also greatly affects the shield construction environment. On the other hand, environmental factors such as temperature and humidity in the environment where the existing grouting slurry is used also have a great impact on its performance, so its adaptability under complex environmental conditions needs to be improved.
[0004] In order to effectively solve the above problems, the present application provides a shield construction grouting slurry and a preparation method thereof. The grouting slurry prepared in the present application has excellent permeability and fluidity, and after its use and curing, it can obtain good crack resistance, waterproofness, stability, temperature resistance and other properties on the basis of ensuring excellent compressive strength. It can solve the problems of insufficient crack resistance, waterproofness and other properties faced by existing grouting slurries for shield construction, and has good environmental adaptability and very excellent application value. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a grouting slurry for shield construction. The raw materials include, by mass: 20 to 35 parts of gel material, 70 to 85 parts of river sand, 20 to 30 parts of fly ash, 15 to 20 parts of limestone powder, 5 to 20 parts of sodium bentonite, 10 to 25 parts of filler, 4 to 10 parts of modified additives, 4 to 6 parts of curing agent, 8 to 10 parts of accelerator, 0.1 to 2 parts of water reducer, and 80 to 110 parts of water.
[0006] As a preferred solution, the mass ratio of the gel material, river sand and filler is (2.5~3.2):(7~8):(1.2~2.4).
[0007] As a preferred solution, the mass ratio of the gel material, river sand and filler is (2.5-3): (7.5-8): (1.5-2.2).
[0008] As a preferred solution, the mass ratio of the gel material, river sand and filler is (2.5-3): (7-7.5): (1.8-2).
[0009] As a preferred solution, the mass ratio of the gel material, fly ash, limestone powder and sodium bentonite is (2.5-3.2): (2.4-2.8): (1.6-2): (1-1.5).
[0010] As a preferred solution, the mass ratio of the gel material, fly ash, limestone powder and sodium bentonite is (2.5-3): (2.5-2.6): (1.8-2): (1.2-1.4).
[0011] As a preferred solution, the gel material is a composition of cement and slaked lime.
[0012] As a preferred solution, the mass ratio of cement to slaked lime is (4-5): (1-1.5).
[0013] As a preferred solution, the mass ratio of cement to slaked lime is (4-4.5):(1-1.2).
[0014] As a preferred solution, the cement is ordinary Portland cement.
[0015] As a preferred solution, the strength grade of the ordinary Portland cement is any one of 32.5, 42.5, 42.5R, and 52.5.
[0016] As a preferred solution, the average particle size of the slaked lime is 200-400 meshes.
[0017] As a preferred solution, the average particle size of the slaked lime is 250-350 meshes.
[0018] As a preferred solution, the sulfur trioxide content of the slaked lime is ≤1.5wt%.
[0019] As a preferred solution, the modulus coefficient of the river sand is 2~3.
[0020] As a preferred solution, the modulus coefficient of the river sand is 2.4~3.
[0021] As a preferred solution, the fly ash is Class C fly ash.
[0022] As a preferred solution, the calcium oxide content of the fly ash is 12-18wt%.
[0023] As a preferred solution, the average particle size of the limestone powder is 60-120 mesh.
[0024] As a preferred solution, the average particle size of the limestone powder is 80-100 mesh.
[0025] As a preferred solution, the filler is modified filling fiber.
[0026] As a preferred scheme, the preparation method of the modified filling fiber includes the following steps: S1: adding basalt fiber and carbon fiber to a mixed solution of water and ethanol, heating to 50-60°C and ultrasonically dispersing at 100-200W for 0.5-1h to obtain a mixed dispersion; S2: adding succinic anhydride and 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65-70°C, keeping warm and stirring for 2-3h, then adding sodium hydroxide to adjust the pH to 7-7.5, and obtaining a pretreated fiber solution after completion; S3: adding ammonia water and tetraethyl orthosilicate to ethanol, and dripping them into the pretreated fiber solution, the dripping time is 1-1.5h, the temperature is 55-60°C, and the temperature is kept warm for 30-50min after the dripping is completed; S4: adding dicyclopentadiene and sodium ethoxide after the insulation is completed, heating to 65-75°C, keeping warm and stirring for 3-4h, and after completion, centrifuging and filtering the product, and vacuum drying to obtain the product.
[0027] As a preferred solution, the mass ratio of the basalt fiber, carbon fiber, succinic anhydride and 3-aminopropyltriethoxysilane is (3-4): (1.3-1.5): (1.2-1.6): (0.5-0.8).
[0028] As a preferred solution, the mass ratio of the basalt fiber, carbon fiber, tetraethyl orthosilicate and dicyclopentadiene is (3-4): (1.3-1.5): (0.5-0.8): (1-1.3).
[0029] As a preferred solution, the mass ratio of the basalt fiber, carbon fiber, tetraethyl orthosilicate and dicyclopentadiene is (3-3.5): (1.3-1.4): (0.7-0.8): (1.1-1.2).
[0030] As a preferred solution, the average diameter of the basalt fiber is 10-15 μm; the average length of the basalt fiber is 6-12 mm.
[0031] As a preferred solution, the average diameter of the carbon fibers is 6-10 μm; and the average length of the carbon fibers is 2-4 mm.
[0032] In the present application, by adding the above-mentioned modified filling fibers, the stability, waterproofness, crack resistance, tensile and compressive strength of the grouting slurry after use can be greatly improved, and good temperature resistance can be maintained. The modified filling fibers in the present application can form a fiber composite of carbon fiber and basalt fiber, and through the active modification of the surface and the connecting effect of silica sol, a multi-layered composite fiber structure can be formed, and through the interface modification on the composite fiber structure, the interaction force and adhesion of the composite fiber in the grouting slurry curing system are significantly enhanced, so that when external forces, especially external tension and impact forces, are applied, it can provide an excellent connecting bridge for the system, and after the interface modification, the wettability of the gel on the surface of the composite fiber can be enhanced to achieve an extension effect, thereby promoting the laying effect of the composite fiber in the grouting slurry. The result is that the formed composite fiber structure can also improve its dispersion and extension angle in the system after curing, and is more suitable for hardness, tensile and crack resistance environments; on the other hand, the modified fiber filler can also provide good heat resistance stability for the grouting slurry. At the same time, the multi-layer superimposed fiber plane structure can greatly increase the water penetration resistance and penetration path in the system after curing, thereby greatly increasing the difficulty of water penetration in a humid environment. The composite fiber structure can help the cured system form a smoother cured surface structure, reduce the aggregation time of the surface hydration layer, increase the initial penetration resistance, and effectively improve the waterproof performance.
[0033] As a preferred solution, the mass ratio of the gel material to the modifying additive is (2.5-3.2): (0.6-0.8).
[0034] As a preferred solution, the modified additive is modified polyacrylamide; the preparation method of the modified polyacrylamide comprises the following steps: S1: adding acrylonitrile, isobornyl acrylate and methyl methacrylate to an acryloyl chloride solution, introducing nitrogen, adding an initiator, heating to 70-75°C and reacting for 3-4 hours; S2: adding acrylamide, deionized water and initiator to the product solution obtained in S1, reacting for 4-8 hours after nitrogen fully replaces the reaction system gas, and obtaining a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 60-65°C and keeping warm for 2-3 hours, adding acetone for cleaning after completion, filtering and drying to obtain the modified product.
[0035] As a preferred solution, the mass ratio of acrylonitrile, isobornyl acrylate, methyl methacrylate and acrylamide is (2-3): (0.5-1): (6-8): (20-28).
[0036] As a preferred solution, the mass ratio of acrylonitrile, isobornyl acrylate, methyl methacrylate and acrylamide is (2-2.5): (0.6-0.8): (7-8): (24-27).
[0037] As a preferred solution, the combined amount of the amylose and epoxy block polyether added is 12-15% of the mass of the modified product solution; the mass ratio of the amylose and epoxy block polyether is (3-4): (1.2-1.5).
[0038] As a preferred solution, the initiator is potassium persulfate.
[0039] The modified additive added in the present application can effectively improve the mechanical properties, waterproofness and stability of the grouting slurry. The modified polyacrylamide in the present application, which contains many and long side molecular chains, can help the extension and dispersion effect of the modified polyacrylamide in the system through its good molecular chain guiding effect in the grouting slurry composite system, greatly increase its adsorption effect on gel particles, and through the barrier effect between gel particles, actively increase the contact difficulty between large-particle gel particles, reduce the probability of collision fusion, avoid excessive aggregation of gel materials in local positions, and improve the overall stability of the grouting slurry; on the other hand, the addition of the linear helical molecular structure of amylose can form a good entanglement network structure with the polyacrylamide molecular chain, thereby enhancing the dispersion effect of the edge gel particles on the system molecular chain, and the generation of this composite structure network effectively increases the connection tightness between the internal particles, sand and molecules after solidification, reduces the penetration speed of water molecules, increases the penetration resistance, and effectively improves the various performances of the grouting slurry when used.
[0040] As a preferred solution, the curing agent is at least one of calcium formate, aluminate and sulphoaluminate.
[0041] As a preferred solution, the curing agent is calcium formate.
[0042] As a preferred solution, the quick-setting agents are sodium silicate and sodium dihydrogen phosphate.
[0043] As a preferred solution, the mass ratio of the sodium silicate to sodium dihydrogen phosphate is (2-3):1.
[0044] As a preferred solution, the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.
[0045] As a preferred solution, the water reducer is a polycarboxylate water reducer.
[0046] As a preferred solution, the water reduction rate of the polycarboxylate water reducer is ≥25%.
[0047] The second aspect of the present application provides a method for preparing the above-mentioned shield construction grouting slurry, and the preparation method comprises the following steps: S1: adding gel material, river sand, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring them in a mixer at 50~60℃ and 150~200rpm for 1~2h to mix them evenly.
[0048] The beneficial effects of this application are:
[0049] 1. The shield construction grouting slurry provided in the present application has excellent permeability and fluidity, and after being cured, it can obtain good crack resistance, waterproofness, stability, temperature resistance and other properties on the basis of ensuring excellent compressive strength. It can solve the problems of insufficient crack resistance, waterproofness and other properties faced by existing shield grouting slurries, and has good environmental adaptability and very excellent application value.
[0050] 2. A shield construction grouting slurry provided in the present application, in which the modified filling fiber added can form a fiber composite of carbon fiber and basalt fiber, and can form a multi-layered composite fiber structure through the active modification of the surface and the connecting effect of silica sol, and through the interface modification on the composite fiber structure, the interaction force and adhesion of the composite fiber in the grouting slurry curing system are significantly enhanced, so that when external forces, especially external tension and impact forces, can provide an excellent connecting bridge for the system, and after the interface modification, the wettability of the gel material on the surface of the composite fiber can be enhanced to extend the effect, thereby promoting the laying effect of the composite fiber in the grouting slurry, and the formed composite fiber structure can also improve its dispersion and extension angle in the system after curing, which is more suitable for hardness, tensile and crack resistance environments.
[0051] 3. The shield construction grouting slurry provided in the present application, the modified filling fiber added to the grouting slurry can also provide good heat resistance stability for the grouting slurry. At the same time, the multi-layer superimposed fiber plane structure can greatly increase the water penetration resistance and penetration path in the system after curing, thereby greatly increasing the difficulty of water penetration in a humid environment. The composite fiber structure can help the system after curing to form a smoother cured surface structure, reduce the aggregation time of the surface hydration layer, increase the initial penetration resistance, and effectively improve the waterproof performance.
[0052] 4. In the present application, a shield construction grouting slurry is provided, in which the added modified additives contain multiple and long side molecular chains, which can help the modified polyacrylamide to extend and disperse in the system through its good molecular chain guiding effect in the grouting slurry composite system, greatly increase its adsorption effect on gel particles, and reduce the probability of collision and fusion through the barrier effect between gel particles, avoid excessive aggregation of gel materials in local positions, and improve the overall stability of the grouting slurry; on the other hand, the addition of the linear helical molecular structure of amylose can form a good entanglement network structure with the polyacrylamide molecular chain, thereby enhancing the dispersion effect of the edge gel particles on the system molecular chain. The generation of this composite structure network effectively increases the connection tightness between the internal particles, sand and molecules after solidification, reduces the penetration rate of water molecules, and provides excellent waterproof performance. DETAILED DESCRIPTION
[0053] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0054] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0055] Example 1
[0056] Example 1 The first aspect provides a grouting slurry for shield construction. The raw materials include, by mass: 26 parts of gel material, 74 parts of river sand, 25 parts of fly ash, 18 parts of limestone powder, 12 parts of sodium bentonite, 18 parts of filler, 6.5 parts of modified additives, 4.5 parts of curing agent, 8.5 parts of accelerator, 0.6 parts of water reducer, and 105 parts of water.
[0057] The gelling material is a composition of cement and slaked lime, and the mass ratio of the two is 4:1.2.
[0058] The cement is ordinary Portland cement with a strength grade of 42.5.
[0059] The average particle size of slaked lime is 320 mesh, and the sulfur trioxide content of slaked lime is 1.2 wt%.
[0060] The modulus coefficient of the river sand is 2.6; the fly ash is Class C fly ash, and the calcium oxide content of the fly ash is 13.2wt%; the average particle size of the limestone powder is 85 mesh.
[0061] The filler is a modified filling fiber, and the preparation method of the modified filling fiber comprises the following steps, calculated by mass: S1: adding 3.3 parts of basalt fiber and 1.32 parts of carbon fiber to a mixed solution of 100 parts of water and 20 parts of ethanol, heating to 60°C and ultrasonically dispersing at 180W for 0.8h to obtain a mixed dispersion; S2: adding 1.55 parts of succinic anhydride and 0.62 parts of 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65°C, keeping warm and stirring for 2.5h, and then adding Add sodium hydroxide to adjust the pH to 7.5, and obtain a pretreated fiber solution after completion; S3: add 1.2 parts of ammonia water and 0.8 parts of tetraethyl orthosilicate to 10 parts of ethanol, and add dropwise to the pretreated fiber solution. The dropping time is 1 hour, the temperature is 55°C, and the solution is kept warm for 40 minutes after the dropping is completed; S4: after the insulation is completed, add 1.2 parts of dicyclopentadiene and 0.12 parts of sodium ethoxide, raise the temperature to 70°C, and stir the reaction for 3.2 hours after insulation. After completion, centrifuge and filter the product, and vacuum dry it to obtain the product.
[0062] The average diameter of the basalt fiber is 12.4 μm, and the average length is 11.2 mm. The basalt fiber was purchased from Jiangxi Shuobang New Materials Co., Ltd.
[0063] The average diameter of the carbon fiber is 8 μm, and the average length is 2.4 mm, and the corresponding size products were purchased from Shenzhen Turing New Materials.
[0064] The modified additive is modified polyacrylamide; the preparation method of modified polyacrylamide comprises the following steps, calculated by mass: S1: adding 2.2 parts of acrylonitrile, 0.68 parts of isobornyl acrylate and 7.5 parts of methyl methacrylate to 25 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 70°C and reacting for 3.5 hours; S2: adding 26.5 parts of acrylamide, 150 parts of deionized water and 0.21 parts of potassium persulfate to the product solution obtained by S1, reacting for 7 hours after nitrogen fully replaces the reaction system gas, and obtaining a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 62°C and keeping warm for 3 hours, adding acetone for cleaning after completion, filtering and drying to obtain the product.
[0065] The combined addition amount of amylose and epoxy block polyether is 13.5% of the mass of the modified product solution; the mass ratio of amylose and epoxy block polyether is 3.6:1.4. Amylose is purchased from Shandong West Asia Chemical, with a linear content of ≥70%; epoxy block polyether is purchased from BASF L-64 model product.
[0066] The curing agent is calcium formate; the accelerating agents are sodium silicate and sodium dihydrogen phosphate, and the mass ratio of the two is 2.2:1.
[0067] The water reducer is a polycarboxylate water reducer, which was purchased from Shandong Bofei Cement Technology Co., Ltd. and has a water reduction rate of 26.2%.
[0068] The second aspect of this embodiment provides a method for preparing the above-mentioned shield construction grouting slurry, the preparation method comprising the following steps: S1: adding gel material, river sand, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring them in a mixer at 60°C and 200rpm for 2h to mix evenly.
[0069] Example 2
[0070] Example 2 The first aspect provides a grouting slurry for shield construction. The raw materials include, by mass: 30 parts of gel material, 80 parts of river sand, 25 parts of fly ash, 18 parts of limestone powder, 12 parts of sodium bentonite, 14 parts of filler, 6 parts of modifying additives, 4.5 parts of curing agent, 8.5 parts of accelerator, 0.6 parts of water reducer, and 105 parts of water.
[0071] The gelling material is a composition of cement and slaked lime, with the mass ratio of the two being 4.5:1.
[0072] The cement is ordinary Portland cement with a strength grade of 42.5.
[0073] The average particle size of slaked lime is 320 mesh, and the sulfur trioxide content of slaked lime is 1.2 wt%.
[0074] The modulus coefficient of the river sand is 2.6; the fly ash is Class C fly ash, and the calcium oxide content of the fly ash is 13.2wt%; the average particle size of the limestone powder is 85 mesh.
[0075] The filler is a modified filling fiber, and the preparation method of the modified filling fiber comprises the following steps, calculated by mass: S1: adding 3.3 parts of basalt fiber and 1.32 parts of carbon fiber to a mixed solution of 100 parts of water and 20 parts of ethanol, heating to 60°C and ultrasonically dispersing at 180W for 0.8h to obtain a mixed dispersion; S2: adding 1.55 parts of succinic anhydride and 0.62 parts of 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65°C, keeping warm and stirring for 2.5h, and then adding Add sodium hydroxide to adjust the pH to 7.5, and obtain a pretreated fiber solution after completion; S3: add 1.2 parts of ammonia water and 0.8 parts of tetraethyl orthosilicate to 10 parts of ethanol, and add dropwise to the pretreated fiber solution. The dropping time is 1 hour, the temperature is 55°C, and the solution is kept warm for 40 minutes after the dropping is completed; S4: after the insulation is completed, add 1.2 parts of dicyclopentadiene and 0.12 parts of sodium ethoxide, raise the temperature to 70°C, and stir the reaction for 3.2 hours after insulation. After completion, centrifuge and filter the product, and vacuum dry it to obtain the product.
[0076] The average diameter of the basalt fiber is 12.4 μm, and the average length is 11.2 mm. The basalt fiber was purchased from Jiangxi Shuobang New Materials Co., Ltd.
[0077] The average diameter of the carbon fiber is 8 μm, and the average length is 2.4 mm, and the corresponding size products were purchased from Shenzhen Turing New Materials.
[0078] The modified additive is modified polyacrylamide; the preparation method of modified polyacrylamide comprises the following steps, calculated by mass: S1: adding 2.2 parts of acrylonitrile, 0.68 parts of isobornyl acrylate and 7.5 parts of methyl methacrylate to 25 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 70°C and reacting for 3.5 hours; S2: adding 26.5 parts of acrylamide, 150 parts of deionized water and 0.21 parts of potassium persulfate to the product solution obtained by S1, reacting for 7 hours after nitrogen fully replaces the reaction system gas, and obtaining a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 62°C and keeping warm for 3 hours, adding acetone for cleaning after completion, filtering and drying to obtain the product.
[0079] The combined addition amount of amylose and epoxy block polyether is 13.5% of the mass of the modified product solution; the mass ratio of amylose and epoxy block polyether is 4:1.2. Amylose is purchased from Shandong West Asia Chemical, with a linear content of ≥70%; epoxy block polyether is purchased from BASF L-64 model product.
[0080] The curing agent is calcium formate; the accelerating agents are sodium silicate and sodium dihydrogen phosphate, and the mass ratio of the two is 2:1.
[0081] The water reducer is a polycarboxylate water reducer, which was purchased from Shandong Bofei Cement Technology Co., Ltd. and has a water reduction rate of 26.2%.
[0082] The second aspect of this embodiment provides a method for preparing the above-mentioned shield construction grouting slurry, the preparation method comprising the following steps: S1: adding gel material, river sand, curing agent, accelerator and water reducer into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring them in a mixer at 60°C and 200rpm for 2h to mix evenly.
[0083] Comparative Example 1
[0084] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the shield construction grouting slurry, measured by mass, include: 26 parts of gel material, 74 parts of river sand, 25 parts of fly ash, 18 parts of limestone powder, 12 parts of sodium bentonite, 6 parts of filler, 6.5 parts of modified additive, 4.5 parts of curing agent, 8.5 parts of accelerator, 0.6 parts of water reducer, and 100 parts of water.
[0085] The mass ratio of cement to slaked lime is 4.2:1.5.
[0086] Comparative Example 2
[0087] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the shield construction grouting slurry, measured by mass, include: 20 parts of gel material, 74 parts of river sand, 25 parts of fly ash, 18 parts of limestone powder, 12 parts of sodium bentonite, 35 parts of filler, 6.5 parts of modified additive, 4.5 parts of curing agent, 8.5 parts of accelerator, 0.6 parts of water reducer, and 110 parts of water.
[0088] Comparative Example 3
[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filling fiber comprises the following steps, calculated by mass: S1: adding 5.5 parts of basalt fiber and 1.8 parts of carbon fiber to a mixed solution of 150 parts of water and 25 parts of ethanol, heating to 60°C and ultrasonically dispersing at 180W for 0.8h to obtain a mixed dispersion; S2: adding 0.58 parts of succinic anhydride and 0.22 parts of 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65°C, and stirring at room temperature; 2.5h, then add sodium hydroxide to adjust the pH to 7.5, and after completion, obtain the pretreated fiber solution; S3: add 1.2 parts of ammonia water and 0.8 parts of tetraethyl orthosilicate to 10 parts of ethanol, and add dropwise to the pretreated fiber solution. The dropping time is 1h and the temperature is 55°C. After the dropping is completed, keep warm for 40min; S4: after the insulation is completed, add 1.2 parts of dicyclopentadiene and 0.12 parts of sodium ethoxide, raise the temperature to 70°C, keep warm and stir to react for 3.2h, and after completion, centrifuge and filter the product, and obtain it after vacuum drying.
[0090] Comparative Example 4
[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filling fiber comprises the following steps, calculated by mass: S1: adding 3.3 parts of basalt fiber and 1.32 parts of carbon fiber to a mixed solution of 100 parts of water and 20 parts of ethanol, heating to 60°C and ultrasonically dispersing at 180W for 0.8h to obtain a mixed dispersion; S2: adding 1.55 parts of succinic anhydride and 0.62 parts of 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65°C, and keeping warm; The mixture was stirred for 2.5 hours, and then sodium hydroxide was added to adjust the pH to 7.5. After completion, a pretreated fiber solution was obtained. S3: 1.2 parts of ammonia water and 0.2 parts of tetraethyl orthosilicate were added to 10 parts of ethanol, and then added dropwise to the pretreated fiber solution. The addition time was 1 hour, and the temperature was 55°C. After the addition was completed, the mixture was kept warm for 40 minutes. S4: After the insulation was completed, 0.6 parts of dicyclopentadiene and 0.05 parts of sodium ethoxide were added, and the temperature was raised to 70°C. The mixture was kept warm and stirred for 3 hours. After completion, the product was centrifuged and filtered, and then dried in vacuo to obtain the product.
[0092] Comparative Example 5
[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average diameter of the basalt fiber is 18.8 μm, the average length is 21 mm, and the corresponding size products are purchased from Jiangxi Shuobang New Materials.
[0094] The average diameter of the carbon fiber is 5 μm, and the average length is 8.2 mm, and the corresponding size products were purchased from Shenzhen Turing New Materials.
[0095] Comparative Example 6
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified polyacrylamide comprises the following steps, calculated by mass: S1: adding 0.5 parts of acrylonitrile, 0.15 parts of isobornyl acrylate and 11.2 parts of methyl methacrylate to 25 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 70°C and reacting for 3.5 hours; S2: adding 26.5 parts of acrylamide, 150 parts of deionized water and 0.21 parts of potassium persulfate to the product solution obtained in S1, reacting for 7 hours after nitrogen fully replaces the reaction system gas, to obtain a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 62°C and keeping warm for 3 hours, adding acetone for cleaning after completion, filtering and drying to obtain.
[0097] Comparative Example 7
[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified polyacrylamide comprises the following steps, calculated by mass: S1: adding 2.2 parts of acrylonitrile, 0.68 parts of isobornyl acrylate and 7.5 parts of methyl methacrylate to 25 parts of acryloyl chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 70°C and reacting for 3.5 hours; S2: adding 26.5 parts of acrylamide, 150 parts of deionized water and 0.21 parts of potassium persulfate to the product solution obtained in S1, reacting for 7 hours after nitrogen fully replaces the reaction system gas, to obtain a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 62°C and keeping warm for 3 hours, adding acetone for washing after completion, filtering and drying to obtain.
[0099] The combined addition amount of amylose and epoxy block polyether is 8.2% of the mass of the modified product solution; the mass ratio of amylose and epoxy block polyether is 5:0.6.
[0100] Performance Evaluation
[0101] Anti-penetration pressure: The anti-penetration pressure test was carried out on the grouting slurries of the embodiments and comparative examples after solidification with reference to the standard GB / T 50082-2009. The results were expressed as the maximum no-water seepage pressure. The test values were the average of 10 tests and recorded in Table 1.
[0102] Compressive strength: The mechanical strength of the grouting slurry obtained in the embodiment and the comparative example was tested after solidification with reference to the standard GB / T 50081-2019. The test value was the average value of 10 tests and recorded in Table 1.
[0103] Tensile strength: The grouting slurry prepared in the embodiment and the comparative example was filled into a 70mm×70mm×20mm mold and compacted and solidified with a scraper. It was cured at a temperature range of 40-45°C and a humidity range of 65-70% for 28 days. After that, the slurry was taken out and tested for its maximum tensile strength at a speed of 5mm / min on a tensile testing machine. The test value was the average value of 10 tests and recorded in Table 1.
[0104] Grouting stability: The grouting slurry prepared in the embodiment and the comparative example was filled into a 40mm×40mm×150mm mold and compacted and solidified with a scraper. The sample was placed in a water tank to ensure that the water overflowed the sample and the water level was 5mm higher than the top of the sample. The storage temperature was in the range of 35-40°C and the ambient humidity was in the range of 65-70%. After 28 days, the sample was removed and the remaining water was allowed to stand, filtered and distilled to obtain a solidified product. The dissolved solid content at 28 days was obtained. The dissolved solid content at 28 days = the mass of the solidified product (g) / the total volume of the remaining water (L). The test value was the average value of 10 tests and recorded in Table 1.
[0105] Table 1 Performance test results
[0106]
[0107] From the examples and comparative examples of the present application and the data results in Table 1, it can be seen that examples 1 and 2 of the present application have obvious performance advantages in terms of stability, waterproofness, temperature resistance and mechanical properties compared to comparative examples 1 to 7. This is mainly because examples 1 and 2 adopt the specific technical solution defined in the present application, which ensures the stability of the grouting slurry itself, improves the resistance and path of water penetration, and strengthens the strength of the internal connection force of the grouting slurry after solidification, thereby improving various performances. However, comparative examples 1 to 7 did not adopt the correct defined technical solution, resulting in their inability to effectively provide the above-mentioned related performances, which further proves the necessity of the defined technical solution of the present application for the technical effect of the present application.
Claims
1. A grouting slurry for shield construction, characterized in that: In parts by mass, the raw materials include: 20-35 parts of gelling material, 70-85 parts of river sand, 20-30 parts of fly ash, 15-20 parts of limestone powder, 5-20 parts of sodium bentonite, 10-25 parts of filler, 4-10 parts of modified additive, 4-6 parts of curing agent, 8-10 parts of accelerating setting agent, 0.1-2 parts of water reducing agent, and 80-110 parts of water; The mass ratio of the gel material, river sand and filler is (2.5-3.2): (7-8): (1.2-2.4); The mass ratio of the gel material, fly ash, limestone powder and sodium bentonite is (2.5-3.2): (2.4-2.8): (1.6-2): (1-1.5); The gel material is a composition of cement and slaked lime; the mass ratio of the cement to slaked lime is (4-5): (1-1.5); The cement is ordinary Portland cement; the strength grade of the ordinary Portland cement is any one of 32.5, 42.5, 42.5R, and 52.5; The average particle size of the slaked lime is 200-400 mesh; the sulfur trioxide content of the slaked lime is ≤1.5wt%; The modulus coefficient of the river sand is 2 to 3; The filler is a modified filling fiber; the preparation method of the modified filling fiber comprises the following steps: S1: adding basalt fiber and carbon fiber to a mixed solution of water and ethanol, heating to 50-60°C and ultrasonically dispersing at 100-200W for 0.5-1h to obtain a mixed dispersion; S2: adding succinic anhydride and 3-aminopropyltriethoxysilane to the mixed dispersion, heating to 65-70°C, keeping warm and stirring for 2-3h, then adding sodium hydroxide to adjust the pH to 7-7.5, and obtaining a pretreated fiber solution after completion; S3: adding ammonia water and tetraethyl orthosilicate to ethanol, and dripping them into the pretreated fiber solution, the dripping time is 1-1.5h, the temperature is 55-60°C, and after the dripping is completed, keeping warm for 30-50min; S4: adding dicyclopentadiene and sodium ethoxide after the insulation is completed, heating to 65-75°C, keeping warm and stirring for 3-4h, after completion, centrifuging and filtering the product, and vacuum drying to obtain the product; The mass ratio of the basalt fiber, the carbon fiber, succinic anhydride and 3-aminopropyltriethoxysilane is (3-4): (1.3-1.5): (1.2-1.6): (0.5-0.8); The mass ratio of the basalt fiber, carbon fiber, tetraethyl orthosilicate and dicyclopentadiene is (3-4): (1.3-1.5): (0.5-0.8): (1-1.3); The average diameter of the basalt fiber is 10-15 μm; the average length of the basalt fiber is 6-12 mm; The modified additive is modified polyacrylamide; the preparation method of the modified polyacrylamide comprises the following steps: S1: adding acrylonitrile, isobornyl acrylate and methyl methacrylate to an acryloyl chloride solution, introducing nitrogen, adding an initiator, heating to 70-75°C for reaction for 3-4 hours; S2: adding acrylamide, deionized water and initiator to the product solution obtained in S1, reacting for 4-8 hours after nitrogen fully replaces the reaction system gas, and obtaining a modified product solution; S3: adding amylose and epoxy block polyether to the modified product solution, heating to 60-65°C for 2-3 hours, adding acetone for cleaning after completion, filtering and drying, and obtaining the modified product solution; The mass ratio of acrylonitrile, isobornyl acrylate, methyl methacrylate and acrylamide is (2-3): (0.5-1): (6-8): (20-28); The combined amount of the amylose and epoxy block polyether added is 12-15% of the mass of the modified product solution; the mass ratio of the amylose and epoxy block polyether is (3-4): (1.2-1.5); The accelerating setting agent is sodium silicate and sodium dihydrogen phosphate; the mass ratio of the sodium silicate to sodium dihydrogen phosphate is (2-3):
1.
2. The shield construction grouting slurry according to claim 1, characterized in that: The average diameter of the carbon fibers is 6-10 μm; the average length of the carbon fibers is 2-4 mm.
3. The shield construction grouting slurry according to claim 2, characterized in that: The fly ash is Class C fly ash; the calcium oxide content of the fly ash is 12-18wt%.
4. The shield construction grouting slurry according to claim 3, characterized in that: The average particle size of the limestone powder is 60-120 meshes.
5. The shield construction grouting slurry according to claim 4, characterized in that: The mass ratio of the gel material to the modified additive is (2.5-3.2): (0.6-0.8).
6. A method for preparing a shield construction grouting slurry according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1: adding gel material, river sand, curing agent, accelerator and water reducing agent into water and mixing and dispersing them evenly; S2: adding the remaining raw materials and stirring them in a mixer at 50-60°C and 150-200rpm for 1-2h to mix them evenly.